When face recognition goes wrong - Havard, Catriona (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"When Face Recognition Goes Wrong explores the myriad ways that humans and machines make mistakes in facial recognition. Adopting a critical stance throughout, the book explores why and how humans and machines make mistakes, covering topics including racial and gender biases, neuropsychological disorders, and widespread algorithm problems. The book features personal anecdotes alongside real-world examples to showcase the often life-changing consequences of facial recognition going wrong. These range from problems with everyday social interactions, through to eyewitness identification leading to miscarriages of justice and border control passport verification. Concluding with a look to the future of facial recognition asking the world's leading experts what are the big questions that still need answered and can we train humans and machines to be super recognizers. This book is a must-read for anyone interested in facial recognition, or psychology, criminal justice, and law"--
Introduction to face recognition and eyewitness identification. -- I recognise your face but who are you? Everyday face recognition errors. -- Unconscious transference and misidentifications. -- The influence of race on face recognition and eyewitness identification -- The influence of gender on face recognition and eyewitness identification -- The influence of age upon face recognition and eyewitness identification -- Machine errors in face recognition -- Disguises, face masks and appearance change. -- Prosopagnosia, Face Blindness. -- Delusions of Misidentification (DMI). -- Super recognisers -- The future of face recognition research.
Keywords: Face perception; Eyewitness identification; Biometric identification; PSYCHOLOGY / General; PSYCHOLOGY / Applied Psychology; PSYCHOLOGY / Cognitive Psychology